Sharia Business Management Strategy in the face of Digital Economy disruption - Izza Dwisaputra; Gunawan Aji (CV Edujavare Publishing, 2026)
this study aims to analyze Sharia business management strategies in the face of digital economic disruption characterized by the rapid development of Information Technology and changes in market behavior. The method used is library research by reviewing various relevant scientific literature from reputable journals and academic books. The results showed that Sharia business management has a strong foundation of values, such as monotheism, justice, and trust, which must be maintained in every business activity. The disruption of the digital economy has a significant impact on Sharia business practices, especially in marketing, finance, and operational aspects, thus demanding innovative adaptations that are still in accordance with Sharia principles. Strategies that can be implemented include sharia-based digitization, strengthening corporate governance, and developing competent and integrity human resources. Thus, the integration between digital technology and Islamic values is the main key in creating a Sharia business that is competitive, sustainable, and provides benefits for the community..